Navigating uncertainty: The dynamics of financial distress and opinion shopping ongoing concern audit opinions in the COVID-19 era - Anggarini, Ni Made Anggi; Sukartha, Putu Dyan Yaniartha; Widhiyani, Ni Luh Sari; Ratnadi, Ni Made Dwi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
This study delves into the intricate relationship between financial distress and opinion shopping in the context of going concern audit opinions, particularly during the challenging COVID-19 pandemic. Focusing on non-financial firms listed on the IDX from 2019 to 2021, the study employed a non-probability, purposive sampling method for selecting relevant samples. Data collection was primarily conducted through non-participant observation, and logistic regression techniques were utilized for analysis. The novelty of this study lies in its temporal focus, situating the analysis within the unique financial and audit challenges posed by the pandemic. One of the key findings is the significant inverse correlation between financial distress, measured by the Altman Z-Score, and the likelihood of receiving a going concern audit opinion. The study demonstrates that increased financial distress significantly raises the probability of a firm receiving a going concern audit opinion. In contrast, the practice of opinion shopping, where firms might switch auditors to obtain a more favorable opinion, is found to decrease the likelihood of receiving such an opinion during the pandemic.